The significance of the sources buildings in Surat Al-A'raf (Journal of the College of Basic Education, 2019)
The Qur'an was and continues to be the focus of attention of learners, and their research in every time and place, it is a rich source of all science and knowledge is inexhaustible, deals with the precise meanings and obeys in a surprising way to the volatility of methods, and helps in the diversification of tricks and color structures, each letter or word or movement Grammatists who have made contributions that are truly a manifestation of the grammatical effort in the Holy Qur'an deserve thanks and praise. To study the different morphological structures, and devise the semantic differences carried by those buildings. Morphological formulas, which have a clear and significant impact on the composition of an important part of the overall meaning of the vocabulary, called the morphological sense .The research consisted of an introduction and a prelude which included two things: the first talked about Surat al-A'raf, and an overview of it, and the second: the definition of the source in the language and terminology, and I have divided my research into three sections, complementing each other, was the title of the first topic: sources of triple verbs Abstract, and the second topic: sources of triple acts increased, and the third topic: the types of structures sources in the Al-A'raf and its significance .I ended my research with a conclusion where I mentioned the most important findings, and finally, praise be to Allah, Lord of the Worlds, and prayers and peace be upon our great Prophet Muhammad and his pure family